Double Jeopardy : Women Who Kill in Victorian Fiction - Morris, Virginia B., 1942- (Book collections on Project MUSE., 1990)
Murder fascinates readers, and when a woman murders, that fascination is compounded. The paradox of mother, lover, or wife as killer fills us with shock. A woman's violence is unexpected, unacceptable. Yet killing an abusive man can make her a cultural heroine. In Double Jeopardy, Virginia Morris examines the complex roots of contemporary attitudes toward women who kill by providing a new perspective on violent women in Victorian literature. British novelists from Dickens to Hardy, in their characterizations, contradicted the traditional Western assumption that women criminals were ""unnatural.